Angiotensin II receptor blockade prevents microangiopathy and preserves diastolic function in the diabetic rat heart. Issue 10 (15th September 2003) - Hayashi, T; Sohmiya, K; Ukimura, A; Endoh, S; Mori, T; Shimomura, H; Okabe, M; Terasaki, F; Kitaura, Y
Abstract : Background: Cardiac microangiopathy may be involved in the development of heart failure in diabetes mellitus. Objective: To evaluate the effect of angiotensin II receptor blockade on cardiac function and fine structures in diabetes. Methods: Male Otsuka Long-Evans Tokushima Fatty (OLETF) rats (n = 30), a model of spontaneously developing diabetes mellitus, and their diabetes resistant counterparts (n = 20) were used. At 30 weeks of age, when the OLETF rats show hyperglycaemic obesity with hyperinsulinaemia, the animals were divided into two groups and given candesartan, an angiotensin II receptor blocker, 0.2 mg/kg/day, or vehicle for six weeks. Capillary density was evaluated in the left ventricular myocardium by electron microscopy, matrix metalloproteinase (MMP) activity by zymography, and cytokines by reverse transcriptase polymerase chain reaction. Results: Compared with the control rats, the OLETF rats at 36 weeks showed decreased peak negative dP/dt (mean (SD): 2350 (250) v 3492 (286) mm Hg/s) and increased cardiomyocyte diameter (24.3 (0.6) v 18.9 (0.6) μm) (both p < 0.05). Thickening of the capillary basement membranes and decreased capillary density were observed. Angiotensin receptor blockade improved almost all the haemodynamic variables, and the histological findings became similar to those of the controls. Angiotensin receptor blockade also activated MMP-2 and prevented an increase of inflammatory cytokines, especially interleukin (IL)-1β and IL-6, in the diabetic heart. Conclusions: Angiotensin II receptor blockade preserved left ventricular diastolic function. It was also potent at improving cardiomyocyte diameter and the thickening of the capillary basement membrane, increasing MMP-2 activity, and decreasing inflammatory cytokines. With all these changes, candesartan could contribute to cardioprotection in diabetes mellitus.